Pameran Hasil Mini Project Sains Anak Terlantar di Kota Makassar - Rifda Nur Hikmahwati Arif; Nurhayani H. Muhiddin; Hasanuddin Hasanuddin; Fandi Ahmad; Siti Nurhalisa (JKM: Jurnal Kemitraan Masyarakat, 2025)
The purpose of this community service is to provide opportunities for street children in Makassar City to exhibit and market their science mini-project products during the Dies Natalis of Universitas Negeri Makassar in 2024. The exhibition was held on the UNM campus, featuring science-based products developed by street children, including decorative lamps, solar panel fan, hand wash soap, tape jusinta, and nata de coco. The implementation method uses an educational exhibition  approach involving street children directly as exhibitors and product sellers. The results of community service activities show that this exhibition not only increases children's confidence in communicating and doing business, but also provides real experience in marketing products to the academic community.